Handbook of Ocean Wave Energy - Pecher, Arthur; Kofoed, Jens Peter (Ocean Engineering & Oceanography, 2017)
Offshore Engineering; Renewable and Green Energy; Numerical and Computational Physics, Simulation; Natural Resource and Energy Economics; Engineering Fluid Dynamics